On the taxonomic status of two large species of East African freshwater crabs: Arcopotamonautes johnstoni (Miers, 1885) from Mount Kilimanjaro and A. platycentron (Hilgendorf, 1897) from Lake Chala (Brachyura: Potamoidea: Potamonautidae) - Cumberlidge, Neil; Daniels, Savel R.; Kipyegon, John K.; Galaszewski, Taylor (Zootaxa, 2026)
The taxonomies of two species of freshwater crabs from Tanzania and Kenya, the river and stream-living A. johnstoni (Miers, 1885) and the threatened lake endemic Arcopotamonautes platycentron (Hilgendorf, 1897) are revised based on examination of the holotypes. Updated diagnoses, illustrations, and distribution maps are provided for these species, and their conservation status is discussed. DNA sequence data of the mitochondrial cytochrome one locus (CO1) between the two aforementioned species indicate a close evolutionary relationship as evident from an unexpectedly low uncorrected CO1 ‘p’ distance of 1.51% that would not normally be considered enough to warrant their recognition as two separate species. On the other hand, it is possible that the distinctly separate habitats of the two species (lake versus streams and rivers) may have given rise in a relatively short evolutionary time for rapid ecological speciation to have produced the numerous morphological changes observed in the lake species.